Disputed memory : emotions and memory politics in Central, Eastern and South-Eastern Europe - Sindbæk Andersen, Tea; Törnquist Plewa, Barbara (Media and cultural memory ;, 2016)
Memories of the crimes of Communism, Nazism and other difficult aspects of the 20th century are fiercely disputed in Central, Eastern and Southeastern Europe. Analyzing representations and negotiations of disputed memories in various media, in local, national and transnational contexts, the chapters in this book emphasize the interconnectedness of memory with emotions, mediation and politics and demonstrate the social impact of memory disputes.